The Lutheran Imaginary That Underpins Social Democracy - Larsen, Mads (Frontiers in Psychology, 2021)
Scandinavian social democracy is increasingly upheld as an alternative that could reform capitalism. The Nordic Model produces income equality, low-conflict politics, and happy people. When half of young Americans express that they would prefer “socialism,” they generally mean to live in a society that provides for its citizens as the Nordics do. Such aspirations are complicated by how social democracy can be viewed as a secularized form of Lutheranism, the Protestant creed that the Nordic region embraced in the sixteenth century. Lutheran norms and values carried into the modern era and made possible social democracy’s two distinguishing features: fascist corporatism and socialist redistribution. A strong state facilitates statist individualism, which empowers individuals vis-à-vis employers, parents, and spouses. The outcome could be cross-culturally salient, as it brings people closer to our species’ fission-fusion baseline. Yet in the modern environment, only Nordics seem to have a cultural imaginary that makes compelling the politics that drive such high levels of both productivity and egalitarianism. The region’s storytelling reflects this Lutheran past and is used to negotiate modern adaptations. A better understanding of social democracy could help prevent that demands for “socialism” motivate a turn to actual socialism.